Factors influencing the utilisation of free-standing and alongside midwifery units in England: a qualitative research study. Issue 2 (17th February 2020) - Walsh, Denis; Spiby, Helen; McCourt, Christine; Grigg, Celia; Coleby, Dawn; Bishop, Simon; Scanlon, Miranda; Culley, Lorraine; Wilkinson, Jane; Pacanowski, Lynne; Thornton, Jim
Abstract : Objective: To identify factors influencing the provision, utilisation and sustainability of midwifery units (MUs) in England. Design: Case studies, using individual interviews and focus groups, in six National Health Service (NHS) Trust maternity services in England. Setting and participants: NHS maternity services in different geographical areas of England Maternity care staff and service users from six NHS Trusts: two Trusts where more than 20% of all women gave birth in MUs, two Trusts where less than 10% of all women gave birth in MUs and two Trusts without MUs. Obstetric, midwifery and neonatal clinical leaders, managers, service user representatives and commissioners were individually interviewed (n=57). Twenty-six focus groups were undertaken with midwives (n=60) and service users (n=52). Main outcome measures: Factors influencing MU use. Findings: The study findings identify several barriers to the uptake of MUs. Within a context of a history of obstetric-led provision and lack of decision-maker awareness of the clinical and economic evidence, most Trust managers and clinicians do not regard their MU provision as being as important as their obstetric unit (OU) provision. Therefore, it does not get embedded as an equal and parallel component in the Trust's overall maternity package of care. The analysis illuminates how implementation of complex interventions in health services is influenced by a range of factors including the medicalisation of childbirth, perceived financial constraints, adequate leadership and institutional norms protecting the status quo. Conclusions: There are significant obstacles to MUs reaching their full potential, especially free-standing midwifery units. These include the lack of commitment by providers to embed MUs as an essential service provision alongside their OUs, an absence of leadership to drive through these changes and the capacity and willingness of providers to address women's information needs. If these remain unaddressed, childbearing women's access to MUs will continue to be restricted.